2007
DOI: 10.1109/jlt.2007.899156
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Limits of Electronic Signal Processing in Direct-Detection Optical Communications

Abstract: Abstract-Electronic signal processing is becoming very attractive to overcome various impairments that affect optical communications, and electronic dispersion compensation (EDC) represents a typical application in the currently designed systems. However, the inherent limits in performance achievable by electronically processing the signal at the output of a nonlinear photodetector have not received the attention they deserve. In this paper, we investigate the information-theoretic limits of electronic signal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In this section, we study the effects of the optical amplification gain on the capacity of amplified noncoherent links (7). Fig.…”
Section: Dependence On Optical Amplification Gainmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we study the effects of the optical amplification gain on the capacity of amplified noncoherent links (7). Fig.…”
Section: Dependence On Optical Amplification Gainmentioning
confidence: 99%
“…Furthermore, optical and electrical filters as well as fiber dispersion can induce ISI. The performance analyses of such systems (with ISI) are limited to numerical calculation of either bit error rate [6] or achievable information rate (AIR) [7]. In this paper, we consider ISI-free communication using advanced signaling [8]- [11] over a fiberoptical system with negligible dispersion (due to short fiber length or the use of dispersion-compensation fibers).…”
mentioning
confidence: 99%
“…In practice, the knowledge of p(y|x) is not required either to compute (2) or to design a system that can achieve it. In the context of optical fiber communications, the AIR has been explicitly used as a practical performance metric, both in linear (e.g., [8]- [10]) and nonlinear scenarios (e.g., [11]- [14]). Based on (1)-(2), the problem of capacity evaluation can be practically subdivided into three parts: the computation of the AIR (2) for given p(x) and q(y|x); the optimization of (2) over q(y|x), which can also be regarded as a channel modeling/estimation problem; and the optimization over p(x), which corresponds to an optimization of the modulation format.…”
Section: ���� ����mentioning
confidence: 99%
“…Several further studies compared the MLSE equalizer to other electronic equalizers and concluded that the MLSE has the best performance regarding the compensation of CD [11] and PMD [12]. Furthermore, the fundamental limits for MLSE equalization in optical communication systems were shown [13], [14].…”
Section: A Historymentioning
confidence: 99%